Beyond Gridlock?: Prospects for Governance in the Clinton Years?and After - Sundquist, James L. (Rowman & Littlefield Publishers, 2010)
For only the second time in close to a quarter century, the U.S. executive and legislative branches are in the hands of the same political party. Will this end governmental gridlock? Or will we discover that the problems of our political system run deeper than party labels? The contributors to this book examine the prospects for unified government during the Clinton presidency and, looking to the future, discuss possibilities for structural reformin the political parties, in campaigning, in the Congress, and through amendments to the Constitution. The book draws on papers and comments presented at a "Government in Gridlock" conference cosponsored by Brookings and the Committee on the Constitutional System shortly after the inauguration of President Clinton. The contributorspresent and former members of Congress and officials of the executive branch, Washington journalists, public opinion analysts, and political scientistsare Howard Baker, James MacGregor Burns, Lloyd Cutler, Thomas Downey, Ken Duberstein, David Gergen, Celinda Lake, Rep. Jim Leach, Thomas Mann, Andrea Mitchell, Tom Oliphant, Howard Paster, Jody Powell, Cokie Roberts, Donald Robinson, Warren Rudman, Barbara Sinclair, Hedrick Smith, and Steven Smith.